A Multilayered Technique for Repair of the Suboccipital Retrosigmoid Craniotomy - Goodarzi, Amir; Ahmadpour, Arjang; Toussi, Atrin; Shahlaie, Kiarash (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective Our primary objective was to retrospectively review our single institution experience using an anatomic multilayered repair of the retrosigmoid suboccipital craniotomy. Our secondary objective was to review the existing body of literature on the repair of this craniotomy and compare our outcomes to previous results.Design Retrospective review of 25 consecutive patients undergoing repair for the retrosigmoid craniotomy.Setting University of California Davis Medical Center (2010–2016).Participants A total of 25 consecutive patients who underwent retrosigmoid craniotomy and repair. Exclusion criteria included patients who were under the age of 18 years.Main Outcome Measures Main outcomes included incidence of postoperative headache, cerebrospinal fluid leak, and wound infections.Results Postoperative headache was reported in two patients in this series (8%). None of the patients in the series developed cerebrospinal fluid leak or wound infections. Mean follow-up period was 16 months.Conclusion Our multilayered anatomic repair after retrosigmoid suboccipital craniotomy results in favorable clinical results and may help reduce the risks associated with this operation.
Keywords: retrosigmoid craniotomy; cranioplasty; CSF leak; headache; repair; skull base; gasket seal